178k views
0 votes
3x + 2y = 5
X – 2y = -1

User Szpic
by
5.2k points

2 Answers

5 votes

Answer: x=3 y=-2

Explanation:

The other dude is wrong, I just did it and got

Marked wrong. It’s (3,-2)

User Vinayak Agarwal
by
4.9k points
4 votes

Answer:

(1, 1 )

Explanation:

Given the 2 equations

3x +2y = 5 → (1)

x - 2y = - 1 → (2)

Adding the 2 equations term by term will eliminate the term in y, that is

(3x + x) + (2y - 2y) = (5 - 1)

4x = 4 ( divide both sides by 4 )

x = 1

Substitute x = 1 in either of the 2 equations and solve for y

Substituting in (1)

3(1) + 2y = 5

3 + 2y = 5 ( subtract 3 from both sides )

2y = 2 ( divide both sides by 2 )

y = 1

Solution is (1, 1 )

User Vedprakash Wagh
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.